The Routledge companion to marketing and sustainability - Peattie, Ken (Routledge, 2025)
"This state-of-the-art handbook provides a comprehensive review of recent research and academic thought on the relationship between marketing and sustainability. It combines a 'micro-marketing' approach considering how to market more sustainable goods and services, with a more critical perspective considering the implications of our marketing systems for the future of the planet and humankind. It also balances a traditional socio-economic perspective on marketing with a physical systems perspective considering how the consequences of our consumption and production systems play out over time and space. Bringing together a range of leading international experts from more than a dozen countries, this unique collection addresses both the environmental side of the sustainability agenda, through topics such as product development, packaging and circular economy initiatives, and its social side through topics such as fair trade marketing, bottom-of-the-pyramid initiatives and marketing ethics. A range of key market contexts are discussed including food, mobility, tourism, luxury consumption and sports along with important developments in the field around social marketing, sustainable lifestyles, new information technologies and the need for better marketing of sustainability. Exploring how marketing can meet the challenge of the transition towards a more sustainable economy and a fairer society, this unique volume will be welcomed by researchers, students, and practitioners from a variety of fields including marketing, business ethics, sociology and environmental studies"-- Provided by publisher.
Keywords: Marketing -- Social aspects.; Sustainability.; Environmental economics.; Marketing.; Marketing; sustainability; Marketing theory and practice; consumers; consumption; production systems; micro-marketing; Environmental impact; Macromarketing; Sustainable product development; sustainable consumption; Circular economy; ethical marketing; sustainable marketing; Social marketing; community action; stakeholder management; elektronické knihy; electronic books